(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Comparative and morphological analysis of flower’s features, such as peculiarities of calyx and corolla (the form and sizes of their hole parts and lobes), stamens (their lengthe, sizes of anthers and widened parts of stamens filaments) and pistil (the lengthe of its style and size of pistil) of four species (С. rotundifolia, С. kladniana, С. polymorpha, С. serrata) from subsection Heterophylla (Nym.) Fed. of genus Campanula L. in the flora of Ukraine were studied. The common features (the form and sizes of calyx, corolla, stamens and pistil), and specific ones (relation of lengthes of calyx’s and corolla’s lobes and their inseparable parts) have been revealed. The seria Кladnianеaе Dremliuga (ser. nov. prov.) has been offered for description.